2014
DOI: 10.1007/s40519-014-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Theory-based psychosocial factors that discriminate between weight-loss success and failure over 6 months in women with morbid obesity receiving behavioral treatments

Abstract: New and relevant findings regarding treatment-induced psychosocial changes might be useful in the architecture of more successful behavioral weight-loss interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
1
8
0
4
Order By: Relevance
“…Substantial inter-correlations among changes in the psychosocial variables could, however, have affected the regression results. The importance of self-regulation change identified here was similarly supported by both theory (Bandura, 2005) and corresponding research with adults (Annesi & Johnson, 2015;Annesi, 2017;Teixeira et al, 2015). However, even given the high importance of a self-regulatory skill focus indicated, some attention to increasing participants' self-efficacy to overcome barriers to physical activity and improving mood should remain, largely because of the considerable volume of research supporting their associations with physical activity in children (Janssen & LeBlanc, 2010;Sallis, Prochaska, & Taylor, 2000).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Substantial inter-correlations among changes in the psychosocial variables could, however, have affected the regression results. The importance of self-regulation change identified here was similarly supported by both theory (Bandura, 2005) and corresponding research with adults (Annesi & Johnson, 2015;Annesi, 2017;Teixeira et al, 2015). However, even given the high importance of a self-regulatory skill focus indicated, some attention to increasing participants' self-efficacy to overcome barriers to physical activity and improving mood should remain, largely because of the considerable volume of research supporting their associations with physical activity in children (Janssen & LeBlanc, 2010;Sallis, Prochaska, & Taylor, 2000).…”
Section: Discussionsupporting
confidence: 63%
“…It was the aim of this research to evaluate effects on enrollees who were above the 90th percentile for BMI by assessing how the treatment influenced the theory-based factors of self-regulatory skills usage, self-efficacy, and mood when contrasted with a control condition of usual care. These three factors were selected because they were consistent with the theories that formed the basis of the treatment, and had been identified as the most salient predictors of physical activity change in research with adults (Annesi & Johnson, 2015). It was thought that improved self-regulatory skills usage would help manage environmental challenges to behavioral changes; increased self-efficacy would emerge from self-regulatory skillsupported successes in dealing with barriers and thus facilitate increased effort and persistence; and improved exercise-induced mood would enable an overall positive climate that would increase self-regulatory effects (Baker & Brownell, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is important to address the psychosocial factors related to nutrition and their impact on health and disease prevention. In case of weight loss success, women with morbid obesity were subjected to cognitivebehavioral methods including education of exercise and healthy eating practices [94]. The study results suggested that the treatment-induced psychosocial changes might be advantageous for more successful behavioral weight-loss management.…”
Section: Preventionmentioning
confidence: 99%
“…In case of weight loss success, women with morbid obesity were subjected to cognitivebehavioral methods including education of exercise and healthy eating practices [94]. The study results…”
Section: Psychosocial Aspect Of Nutrition and Disease Preventionmentioning
confidence: 99%